MENINGKATKAN KETERAMPILAN MOTORIK HALUS ANAK MELALUI KEGIATAN MEWARNAI GAMBAR DENGAN PASIR BERWARNA PADA ANAK USIA (5-6) TAHUN DI TK TABITHA 1 KELURAHAN BENTENG KOTA AMBON - Gracia Sitaniapessy; Rosmaryn Tutupary; Junita. L. Kundre (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the low development of fine motor skills among 5–6-year-old children at TK Tabitha 1 Benteng, Ambon City, characterized by poor hand–eye coordination, difficulty grasping pencils, and limited dexterity during coloring activities due to insufficient stimulation and monotonous learning methods. The research aimed to improve children's fine motor skills through coloring activities using colored sand. Employing a classroom action research design based on Kurt Lewin's model, the study was conducted over two cycles comprising four meetings with 13 children as subjects. Data were collected through observation sheets and documentation, then analyzed descriptively. Results showed significant improvement: in the pre-cycle, 61.53% of children were categorized as "belum berkembang" (not yet developed); after Cycle I, 53.84% remained in this category; and by Cycle II, 0% were in the lowest category while 76.92% achieved "berkembang sangat baik" (very well developed). Indicators such as hand movement control, shape imitation, media exploration, and speed regulation improved markedly. The findings confirm that colored sand coloring activities effectively enhance fine motor skills in early childhood.